2022
DOI: 10.3390/antiox11050894
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Inflammation, Oxidative Stress and Cardiovascular Health in Children and Adolescents: A Systematic Review

Abstract: Recent studies indicate that cerebrovascular diseases and processes of atherosclerosis originate in the childhood era and are largely influenced by chronic inflammation. Some features of vascular dysfunction in adulthood may even be programmed prenatally via genetic influences and an unfavorable intrauterine milieu. Oxidative stress, defined by an imbalance between the production and generation of reactive oxygen species (ROS) in cells and tissues and the capability of an organism to scavenge these molecules v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 180 publications
1
15
0
Order By: Relevance
“…In FH patients, oxidative stress is a major factor in the onset and development of atherosclerosis. It is reported that hypercholesterolemia causes the production of superoxide radicals, which inhibits the activity of endothelial nitric oxide synthase (eNOS), lowering NO bioavailability as an antioxidant resulting in an inflammatory response in the artery wall [ 57 , 58 ].…”
Section: Molecular Mechanisms Of Pro- and Antioxidant Towards Cvdmentioning
confidence: 99%
“…In FH patients, oxidative stress is a major factor in the onset and development of atherosclerosis. It is reported that hypercholesterolemia causes the production of superoxide radicals, which inhibits the activity of endothelial nitric oxide synthase (eNOS), lowering NO bioavailability as an antioxidant resulting in an inflammatory response in the artery wall [ 57 , 58 ].…”
Section: Molecular Mechanisms Of Pro- and Antioxidant Towards Cvdmentioning
confidence: 99%
“…Caries is characterized by the same etiological factors that lead to other chronic non-communicable diseases that are associated with increased dietary sugar intake, such as cardiovascular disease, diabetes, and obesity. There is strong evidence that there is a link between oral diseases and chronic systemic disorders ( 33 , 34 ). Although numerous studies have looked into the links between chronic systemic and dental conditions, it is still unclear how this information can be applied in clinical practice, particularly when it comes to pediatric patients ( 41 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…The rationale was that dental caries could increase the risk of systemic inflammation in a variety of ways ( 33 ). For example, among hypertensive pediatric patients with poor oral status, the intensive oxidation of several plasma substrates, increase in reactive metabolites of oxygen, lipid peroxidation, inactivation of prostacyclin and nitric oxide and an imbalance in the total antioxidant capacity were noted ( 34 36 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nearly 50 % of all heart attacks and strokes occur in patients with normal cholesterol levels [ 9 ]. Furthermore, oxidative stress and micro-inflammation are more complex and intimately linked with cardiovascular disease [ 10 ].…”
Section: Introductionmentioning
confidence: 99%